Reinventing Government dan Pemberdayaan Aparatur Pemerintah Daerah - Annisa Citra Fatikha (Institut Pemerintahan Dalam Negeri (IPDN), 2016)
Decentralization and region autonomy demand local government in United State of Republic Indonesia to become more independent and increase its work level in managing its potential and increase the society participation in policy implementation. Government apparatus is the smallest component in governance that can determine succeed of governance process and service providing to society. Reinventing government is a concept to bureaucracy that can grow entrepreneur soul in governance apparatus and more increasing apparatus work level as an effort to achieve the purpose of local government organization. Concept of reinventing government can be an answer from the problem of local governance bureaucracy if its implementation is appropriate or not with the condition of economy, social, politic, and culture and also got the support from government aspect, entrepreneur, and society.